2008
DOI: 10.1002/jso.21093
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic significance of mucin phenotype in gastric cancer

Abstract: Mucin phenotype has a significant prognostic value and may be a useful marker for the treatment of human gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 31 publications
5
55
6
Order By: Relevance
“…Lee et al 6 reported that the mucin intestinal phenotype was associated with a significantly better prognosis. In contrast, Wakatsuki et al 7 found that the same immunophenotype was associated with a significantly worse prognosis and a higher rate of postoperative liver metastasis. Notably, many different antibodies have been used to evaluate mucin expression, as well as different cutoff values for the definition of mucin positivity, leading us to speculate that these differences are responsible for the inconsistent results.…”
Section: Survival Of Gastric Cancer With Respect To Mucin Expressionmentioning
confidence: 90%
See 4 more Smart Citations
“…Lee et al 6 reported that the mucin intestinal phenotype was associated with a significantly better prognosis. In contrast, Wakatsuki et al 7 found that the same immunophenotype was associated with a significantly worse prognosis and a higher rate of postoperative liver metastasis. Notably, many different antibodies have been used to evaluate mucin expression, as well as different cutoff values for the definition of mucin positivity, leading us to speculate that these differences are responsible for the inconsistent results.…”
Section: Survival Of Gastric Cancer With Respect To Mucin Expressionmentioning
confidence: 90%
“…Adenocarcinomas with at least 10% reactivity for each mucin gene antibody were identified as positive as previously reported. 7,8,13 Mucin phenotypes were further subdivided into gastric (only gastric mucin positive) and gastricpredominant gastrointestinal phenotypes and intestinal (only intestinal mucin positive) and intestinal-predominant gastrointestinal phenotypes and null type based on the combination of predominant patterns of MUC5AC, MUC2, MUC6, and CD10 staining according to Tsukashita et al 17 We defined gastric cancer with gastric mucin predominant type (GC-GP) as gastric type plus gastric-predominant gastrointestinal phenotypes (gastric type þ gastric-predominant gastrointestinal type) and gastric cancer with intestinal mucin predominant type (GC-IP) as intestinal type plus intestinal-predominant gastrointestinal phenotypes (intestinal type þ intestinal-predominant gastrointestinal type) for comparison based on the predominant mucin expression.…”
Section: Immunohistochemical Staining For Mucin Phenotypesmentioning
confidence: 99%
See 3 more Smart Citations